Appraising the Moderation Indonesian Muslims with Special Reference to Muhammadiyah and Nahdlatul Ulama - Zarkasyi, Hamid Fahmy (LPPM IAIN Kudus, 2018)
Indonesia is the country that has been widely regarded as home to a moderate brand of Islam compared to the more assertive political and militant Islamic revivals that have taken place in some of Middle East countries. However, recent series of terrorist attack and the emergence of groups that are categorized as extremist and fundamentalist in Indonesia have given opposite impression. This paper is aimed at appraising the the moderation of Indonesian Muslim. The object of this study is two largest Muslim organizations namely Muhammadiyah and Nahdlatul Ulama. For this appraisal the author employs the selectively the criteria of Western scholars as well as Muslim intellectuals, since there are growing tendency of observers, intellectual and policy makers to pose certain criteria of moderation based on their own interests. General survey on those tendencies suggests that there are at least three categories of moderate definition: extremist, Western biased and Islamic criteria, each of which contain acceptable and unacceptable aspects that require further selection. It is from these acceptable criteria that the author attempts to appraise the moderation of Indonesian Muslims through the vision and mission of mass-organization, especially Muhammadiyah and Nahdlatul Ulama as well as their education system. The study arrive on the conclusion that based on Islamic as well as Western criteria, the majority of Indonesian Muslims or the mainstream remain moderate.